Comparison study between popular brands of coffee, tea and red wine regarding polyphenols content and antioxidant activity - Pintać, Diandra; Bekvalac, Kristina; Mimica-Dukić, Neda; Rašeta, Milena; Anđelić, Nikola; Lesjak, Marija; Orčić, Dejan (Food chemistry advances, 2022)
•Chemical composition and antioxidant assays results were expressed as 200 mL servings.•Green tea serving showed highest antioxidant potential and content of polyphenols.•Turkish and instant coffees displayed lower activity and number of detected compounds.•Similar compounds in different concentrations were detected in teas and wines. This study compared the phenolic profile and antioxidant activity, expressed by real serving's concentrations, of most popular plant-based drinks: coffee, tea and wine. Popular brands of coffees, black and green teas and red wines were subjected to LC–MS/MS analysis of 47 phenolic compounds known for their beneficial effect on human health, measurement of total phenolic, tannins and flavonoids contents as well as various in vitro antioxidant assays. Each drink group was characterized by specific compounds and an analogy was drawn between composition and exhibited antioxidant activity. With only phenolic acids and coumarins detected in their composition, coffees showed moderate antioxidant activity in all assays. Teas had the highest antioxidant potential, particularly green tea, with great amounts of gallic and ellagic acids, hyperoside, quercetin 3-O-glucoside, rutin, kaempferol 3-O-glucoside, vitexin, catechin, epicatechin and epigallocatechin gallate present in servings. Red wines showed good antioxidant activity, with great similarity in detected compounds to teas with a few exceptions – myricetin, resveratrol and vanillic acid. By results from this study, it could be concluded that green tea 200 mL serving, when compared with the same of black tea, Turkish and instant coffee, and red wine, has the highest antioxidant activity and content of beneficial polyphenols.